Expression of Values as a Criterion for the Suitability of Volunteers to Provide Assistance to Children from Families Facing Social Risks - Klanienė, Ilona; Zamrykit, Aleksandra (Social Welfare: Interdisciplinary Approach, 2026)
In Lithuania, assistance to children growing up in families facing social risks is provided by non-governmental organisations, which engage volunteers after assessing their suitability for working with children. The present article reveals the expression of the values of volunteers as an essential criterion for selection for work with children from families facing social risks. The article presents the results of a quantitative study obtained by using various instruments: a written questionnaire was used to assess volunteers’ involvement in voluntary activities, satisfaction with activities, etc.; the Schwartz basic human values questionnaire helped identify the core values of volunteers, the Thomas-Kilmann instrument helped reveal the conflict resolution strategies used by volunteers and their links to the expression of values. The study involved 102 volunteers working with children in NGOs. The results of the quantitative study revealed links between the volunteers’ successful long-term activities and the expression of values. According to the results of the quantitative study, it can be stated that the expression of values should become one of the essential criteria when selecting volunteers to work with children from families facing social risks.